Mental Causation A Counterfactual Theory - Kroedel, Thomas (Humanities, 2019)
This book presents a comprehensive account of how the mind causes things to happen in the physical world. It will be of interest to a range of readers in philosophy of mind, metaphysics, and philosophy of science. This book is also available as Open Access.